Innovative Application of IP Microwave in Broadband GPON (PON) Network - Guo, Pengcheng (Journal of Theory and Practice of Engineering Science, 2025)
Municipal renovation is frequent, often resulting in the main trunk of broadband communities being excavated. The construction site is complex, the repair time is long, and there are often repeated failures. If the site conditions do not meet the requirements for emergency access, some failures can be interrupted for up to a week. Broadband users in the community are offline for a long time, leading to upgrade complaints and poor customer perception. This project adopts the technical principles of PON/GPON protocol, Ethernet protocol, wireless microwave protocol, and data signal interaction technology to achieve temporary communication of broadband community backbone. The communication scenario is not affected by on-site construction, and the deployment is simple and convenient, which is conducive to shortening the fault time and improving user perception.